Clinical Finding, Diagnosis, and Management of Tuberculous Mastoiditis in 4 Cases - Sally Mahdiani; Lina Lasminingrum; Bambang Purwanto; Riri Handayani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Tuberculous mastoiditis is a rare case of chronic otitis media disease and extrapulmonary tuberculosis, caused by Mycobacterium tuberculosis. Case Presentation: Four cases of tuberculous mastoiditis were reported, ranging in age from 16 to 66 years. All patients presented with chronic discharge with signs of mastoiditis with intra and extratemporal complications. Two patients only manifested in the mastoid and two other patients had symptoms of tuberculosis in other organs, especially the lungs. All patients underwent radical mastoidectomy and histopathological examination showed tuberculosis. All patients received category 1 and category 2 antituberculosis drugs. Conclusion: The clinical features of tuberculous mastoiditis vary. Diagnosis of tuberculous mastoiditis can be done by histopathological examination and geneXpert. Surgical therapy and administration of antituberculosis are the main options in the management of tuberculous mastoiditis.